Ceramic structure

By adopting a two-layer ceramic structure, the first layer with high crystallinity and the second layer with low crystallinity, combined with the void structure, the improvement of the ceramic structure in terms of durability is solved, and the stability and corrosion resistance are improved under high temperature and mechanical stress are achieved.

CN119731136APending Publication Date: 2025-03-28KYOCERA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380063674.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-09-06
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

There is room for improvement in the durability of existing ceramic structures, especially in terms of stability and corrosion resistance under high temperatures and mechanical stresses.

Method used

A ceramic structure adopts a bilayer structure, wherein the first layer consists of ceramic materials such as AlN with high crystallinity, and the second layer is located above the first layer, AlN crystal particles with low crystallinity, and a void structure is introduced into the second layer to reduce residual stress.

Benefits of technology

The durability of the ceramic structure has been significantly improved, and it can maintain stability and corrosion resistance under high temperature and mechanical stress, and extend its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731136A_ABST
    Figure CN119731136A_ABST
Patent Text Reader

Abstract

The ceramic structure has: a first layer having first crystal particles; and a second layer over the first layer and having second crystal particles. Each of the first crystal particles and the second crystal particles contains one or more metal elements selected from the group consisting of Al, Si, Ti, Cr, Zr and Y and one or more non-metal elements selected from the group consisting of N, C and B. The first crystal particles and the second crystal particles are the same compound. When W1 is the half-value width of the peak value of the Miller index of the maximum intensity of the first crystal particles in X-ray diffraction of the first layer, and W2 is the half-value width of the peak value of the same Miller index of the second crystal particles in X-ray diffraction of the second layer, 9 * W1 > W2 > W1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The disclosed embodiments relate to ceramic structures. Background Art

[0002] As described in Patent Document 1, a ceramic structure having a thin film formed by chemical vapor deposition (CVD) is known. Patent Document 2 states that the film formed by chemical vapor deposition is dense and has no pores and has high smoothness. In addition, Patent Document 3 states that the content of pores is less than 3% by area.

[0003] Prior Art Literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 63-40314

[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 7-180057

[0007] Patent Document 3: Japanese Patent Application Publication No. 2020-53579 Summary of the invention

[0008] A ceramic structure of one embodiment has: a first layer having first crystal particles; and a second layer located on the first layer and having second crystal particles. The first crystal particles and the second crystal particles respectively contain one or more metal elements selected from Al, Si, Ti, Cr, Zr and Y and one or more non-metal elements selected from N, C and B. The first crystal particles and the second crystal particles are the same compound. When the half-value width of the peak of the Miller index of the maximum intensity of the first crystal particle in the X-ray diffraction of the first layer is set to W1, and the half-value width of the peak of the second crystal particle in the X-ray diffraction of the second layer that is the same as the Miller index is set to W2, 9×W1>W2>W1.

[0009] Effects of the Invention

[0010] According to one aspect of the embodiment, a ceramic structure having excellent durability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a cross-sectional view showing an example of a ceramic structure according to an embodiment.

[0012] Figure 2 yes Figure 1 An enlarged view of area A is shown.

[0013] Figure 3It is a cross-sectional view showing another example of the ceramic structure according to the embodiment.

[0014] Figure 4 It is a cross-sectional view showing another example of the ceramic structure according to the embodiment.

[0015] Figure 5 It is a cross-sectional view showing another example of the ceramic structure according to the embodiment.

[0016] Figure 6 This is a flowchart showing an example of a method for producing a ceramic structure according to an embodiment. DETAILED DESCRIPTION

[0017] In the above-mentioned configuration, there is room for further improvement in terms of improving durability.

[0018] Therefore, it is desired to provide a ceramic structure having excellent durability.

[0019] Hereinafter, embodiments of the ceramic structure disclosed in the present application will be described with reference to the drawings. It should be noted that the present disclosure is not limited to the embodiments described below.

[0020] <Implementation Method>

[0021] Figure 1 1 is a cross-sectional view showing an example of a ceramic structure according to an embodiment. Figure 1 In the example shown, the ceramic structure 1 has a first layer 10 and a second layer 20. The first layer 10 has a first crystal particle 11. The second layer 20 has a second crystal particle 21. The first crystal particle 11 and the second crystal particle 21 each contain one or more metal elements selected from Al, Si, Ti, Cr, Zr and Y and one or more non-metal elements selected from N, C and B.

[0022] The first layer 10 may contain 50% by area or more of the first crystal particles 11. The first layer 10 may contain 80% by area or more of the first crystal particles 11. The first layer 10 may contain 90% by area or more of the first crystal particles 11.

[0023] The second layer 20 may contain 50 area % or more of the second crystal particles 21. The second layer 20 may contain 80 area % or more of the second crystal particles 21. The second layer 20 may contain 90 area % or more of the second crystal particles 21.

[0024] In addition, the amount of the second crystal particles 21 contained in the second layer 20 may be greater than the amount of the first crystal particles 11 contained in the first layer 10. The first crystal particles 11 and the second crystal particles 21 are the same compound. The first crystal particles 11 and the second crystal particles 21 may be any one of AlN, Si3N4, SiC, TiN, TiC, ZrN, ZrB, and YN. In particular, the first crystal particle 11 may be AlN. The so-called same compound means, for example, in the case of AlN, as long as it can be identified as AlN by XRD with Al and N as the main components. For example, Al and N may not be contained in a one-to-one ratio. The Al content may also be different between the first crystal particle 11 and the second crystal particle 21.

[0025] When the half-value width of the peak of the Miller index of the maximum intensity of the first crystal particle 11 in the X-ray diffraction of the first layer 10 is set to W1, and the half-value width of the peak of the second crystal particle 21 in the X-ray diffraction of the second layer 20 The same as the Miller index is set to W2, 9×W1>W2>W1. The half-value width is known as an index for evaluating the crystallinity of a crystal. When the same compounds are compared with each other, the crystal with a smaller half-value width has higher crystallinity. That is, W2>W1 means that the crystallinity of the second crystal particle 21 is lower than the crystallinity of the first crystal particle 11. In addition, 9×W1>W2 means that the half-value width of W2 is less than 9 times the half-value width of W1. The relationship between W1 and W2 can also be 8.5×W1>W2. The relationship between W1 and W2 can also be 8.0×W1>W2. The relationship between W1 and W2 can also be 6.9×W1>W2.

[0026] W1, W2 and W3 described later can be measured by the following method. Use the thin film X-ray diffraction device X'Pert PRO-MRD (DY1878) manufactured by PANalytical for low-angle incidence measurement. The optical system is an X-ray reflector (automatically inserted attenuation plate, mask 5, Soller slit 0.02rad, slit 1 / 8), flat collimator, tube: CuKα, X-ray: 45kV, 40mA, 2θ scan: 10°~100°, incident angle: 0.1°, step: 0.02°, time: 4.0 seconds / step. For example, whether the crystal particle is AlN can be judged based on JCPDS No.00-025-1133.

[0027] exist Figure 1 In the example shown, the first layer 10 is a substrate, which may also have a substantially disk shape, for example. Figure 1 In the example shown, the second layer 20 may also be located on the base (the first layer 10 ), and the second layer 20 is in contact with the base (the first layer 10 ).

[0028] The substrate (first layer 10) contains, for example, ceramics such as aluminum nitride (AlN) as a main component. In addition, the first layer 10 may also contain, for example, aluminum oxide (Al2O3), yttrium oxide (Y2O3), etc. as a main component. In addition, the first layer 10 may also be a sintered body obtained by firing a raw material powder. When the first layer 10 is a sintered body, the first crystal particles 11 have a high degree of crystallinity. If such a structure is provided, a ceramic structure with excellent durability can be provided.

[0029] In addition, first crystal particles 11 and second crystal particles 21 may be hexagonal crystals. In the case of hexagonal crystals, the crystals have anisotropy, and by utilizing this anisotropy, a ceramic structure having excellent durability can be provided.

[0030] In addition, the first crystal particle 11 and the second crystal particle 21 are AlN, and the difference between W1 and W2 (W2-W1) can be 0.1° or more and 0.6° or less. With such a structure, the second layer 20 different from the first layer 10 can be provided, and the difference in the physical property values ​​between the first layer 10 and the second layer 20 can be reduced, so that a ceramic structure with excellent durability can be provided.

[0031] The second layer 20 may also have a void 22 located inside the second layer 20. The void 22 may be long in the thickness direction of the second layer 20, and both ends in the thickness direction may be blocked. The void 22 may also have at least one of a first void 22a in which one end in the thickness direction is connected to the first layer 10 and a second void 22b separated from the first layer 10 at one end. By having such a structure, for example, the residual stress inside the second layer 20 can be reduced. Therefore, it is not easy to cause peeling and cracking between the first layer 10 and the second layer 20, and the durability of the ceramic structure 1 is improved.

[0032] The void 22 may also have a longitudinal shape that is longer in the thickness direction than the width direction of the second layer 20. Regarding the void 22, both ends of the thickness direction of the second layer 20 may also be blocked. That is, the void 22 is located between the first surface 201 of the second layer 20 opposite to the first layer 10 and the second surface 202 on the opposite side of the first surface 201, and is not exposed at the interface with the outside, that is, the second surface 202. Therefore, even if the second layer 20 has a void 22 inside, it has the desired durability. The void 22 is not a lattice defect or a so-called nanopore that may exist in the second crystal particle 21. The width of the void 22 may be, for example, 0.01 μm or more. The width of the void 22 may also be, for example, 0.05 μm or more. The width of the void 22 may also be, for example, 1 μm or less. The width of the void 22 may also be, for example, 0.5 μm or less. The length of the void 22 may be, for example, 0.2 μm or more. The length of the void 22 may also be, for example, 0.5 μm or more. The length of the gap 22 may be, for example, 5 μm or less. The length of the gap 22 may be, for example, 1 μm or less.

[0033] The presence or absence of the void 22 can be confirmed, for example, by observation using an electron microscope. The area ratio of the void 22 in the second layer 20 can be, for example, 0.2 area % or more. The area ratio of the void 22 can also be, for example, 1 area % or more. The area ratio of the void 22 can also be, for example, 5 area % or less. The area ratio of the void 22 can also be, for example, 3 area % or less. The measurement of the area ratio of the void 22 in the second layer 20 can be performed, for example, in the central part of the cross section after the cross section of the second layer 20 is mirror-finished. Observation using an electron microscope can be performed at a magnification of 1000 to 50000 times. The electron microscope uses, for example, JSM 7900F manufactured by JEOL, with an accelerating voltage of 5.0KV. The area ratio of the void 22 can be calculated based on the SEM photograph using the image analysis software IMAGE Pro 10 manufactured by MEDIA CYBERNETICS. At this time, the SEM photograph can also be binarized using the Ward method and the binarized image can be used for calculation.

[0034] In addition, the void 22 may also include a first void 22a and a second void 22b. The first void 22a is a void 22 in which one end, i.e., the lower end, of the second layer 20 in the thickness direction is in contact with the surface 101 of the first layer 10. The second void 22b is a void 22 in which one end is separated from the surface 101 of the first layer 10. The second layer 20 may include both the first void 22a and the second void 22b inside, or may include only one of them.

[0035] Next, use Figure 2 The second layer 20 will be described in further detail. Figure 2 yes Figure 1 An enlarged view of area A is shown.

[0036] The second crystal particles 21 of the second layer 20 may also have columnar crystals 21a. The columnar crystals 21a extend, for example, in a direction intersecting the surface 101 of the first layer 10. That is, the columnar crystals 21a extend in the thickness direction of the second layer 20. The second layer 20 may also have a plurality of columnar crystals 21a arranged along the surface 101 of the first layer 10. Since the second crystal particles 21 have the columnar crystals 21a, the thermal conductivity in the thickness direction of the second layer 20 is improved. Therefore, the deviation of the temperature in the thickness direction of the second layer 20 is reduced, and the durability is improved.

[0037] In addition, regarding the width of the void 22, that is, the length of the void 22 along the surface 101 of the first layer 10, the second end 222 away from the first layer 10 can be smaller than the first end 221 in the thickness direction located on the first layer 10 side. As a result, it is difficult for the void 22 to become a crack and expand from the second end 222 to the direction of the second surface 202. Therefore, the durability of the ceramic structure 1 including the second layer 20 is improved. The void 22 can also be located between adjacent columnar crystals 21a. The void 22 can be larger than the columnar crystal 21a, or smaller than the columnar crystal 21a.

[0038] In addition, there may be a space 40 between the first layer 10 and the second layer 20. Here, the space 40 refers to a space extending along the surface 101 of the first layer 10. More specifically, in cross-sectional observation, the length of the space 40 along the direction of the surface 101 is connected by an imaginary line segment, which is longer than the maximum height of the space 40 in the direction intersecting the surface 101. More specifically, the length of the space 40 along the direction of the surface 101 is connected by an imaginary line segment, which is more than 5 times the height of the space 40 in the direction intersecting the surface 101, and preferably more than 10 times.

[0039] The porosity of the portion of the second layer 20 close to the first layer 10, i.e., the first portion, may be greater than the porosity of the portion of the second portion that is farther from the first layer 10 than the first portion. Thus, the thermal conductivity of the first portion can be made smaller than the thermal conductivity of the second portion. Therefore, when a thermal shock is applied to the ceramic structure 1 from the side of the second layer 20, a sharp change in the temperature difference generated between the first layer 10 and the second layer 20 is suppressed. As a result, the durability of the ceramic structure 1 against thermal shock is improved. It should be noted that the first portion may be, for example, an area including the first surface 201 in the above-mentioned SEM image, and the second portion may be, for example, an area including the second surface 202 in the above-mentioned SEM image. In addition, the first portion and the second portion may also be partially overlapped.

[0040] Figure 3 to Figure 5 FIG. 2 is a cross-sectional view showing another example of a ceramic structure according to an embodiment of the present invention. Figure 3As shown, the second layer 20 may also have a plurality of columnar crystals 21a that are inclined relative to the surface 101 of the first layer 10. In addition, the gaps 22 may also be located between the adjacent plurality of columnar crystals 21a. Thus, if the front end of the columnar crystal 21a is in contact with the gap 22, the residual stress of the columnar crystal 21a is reduced, and thus the durability of the second layer 20 is improved. It should be noted that in Figure 3 In the figure, as an example of the gap 22, the first gap 22a is shown, but the second gap 22b may also be used.

[0041] In addition, if Figure 4 As shown, the first layer 10 may also have projections and depressions on the surface 101 opposite to the second layer 20. In addition, the first end portion 221, which is one end of the void 22 in the thickness direction, may also be located in the recessed portion 101b of the first layer 10. Thus, the void 22 is prevented from expanding in the direction along the surface 101 of the first layer 10 at the first end portion 221. As a result, the generation of cracks in the columnar crystals 21a adjacent to the first end portion 221 is suppressed, and the durability of the ceramic structure 1 is improved. The same is also true for the case where the void 22 is located on the projection 101a of the first layer 10. It should be noted that in Figure 4 In the figure, as an example of the void 22, the first void 22a is shown, but the second void 22b may also be used. In addition, the void 22 may also be located on the convex portion 101a of the first layer 10. In addition, Figure 4 In the description, an example is given in which the plurality of columnar crystals 21 a extend in the thickness direction of the second layer 20 , but the columnar crystals 21 a may extend obliquely with respect to the thickness direction of the second layer 20 in a manner corresponding to the irregularities of the surface 101 of the first layer 10 .

[0042] The volume resistivity of the second layer 20 at 25° C. may be greater than the volume resistivity of the first layer 10 at 25° C. The volume resistivity of the second layer 20 at 500° C. may be greater than the volume resistivity of the first layer 10 at 500° C. The volume resistivity of the second layer 20 at 25° C. may be 1×10 12 Ω·m or more. The volume resistivity of the second layer 20 at 500°C may be 1×10 5 Ω·m or more.

[0043] The volume resistivity of the second layer 20 or the first layer 10 can also be measured by a three-terminal method in accordance with JIS C 2141:1992.

[0044] The ceramic structure 1 may have a conductive layer inside. The conductive layer may have a heater function. In addition, the conductive layer may also have an adsorption function. The conductive layer may have W, Mo, Ni, Pt, etc. as a metal.

[0045] In addition, if Figure 5As shown, the ceramic structure 1 may also have a third layer 30 located between the first layer 10 and the second layer 20. The third layer 30 contains third crystal particles 31 which are the same compound as the second layer 20. The third layer 30 may also have the third crystal particles 31 as a main component. The third layer 30 may contain more than 50 area % of the third crystal particles 31. The third layer 30 may also contain more than 80 area % of the third crystal particles 31. The third layer 30 may also contain more than 90 area % of the third crystal particles 31.

[0046] When the half-value width of the peak value identical to the Miller index of the second crystal particle 21 in the X-ray diffraction of the third layer 30 of the third crystal particle 31 is set to W3, W2>W3 can also be satisfied. In addition, 9×W3>W2 can also be satisfied. The relationship between W3 and W2 can also be 8.5×W3>W2. The relationship between W3 and W2 can also be 8.0×W3>W2. The relationship between W3 and W2 can also be 6.9×W3>W2. If such a structure is provided, the same effect as that of the first layer 10 and the second layer 20 can be obtained.

[0047] <Method for producing ceramic structure>

[0048] use Figure 6 An example of a method for producing a ceramic structure will be described. Figure 6 This is a flowchart showing an example of a method for producing a ceramic structure according to an embodiment.

[0049] A sintered body containing 90% to 99.9% by mass of disc-shaped AlN as a substrate (first layer 10) is prepared. And, a second layer mainly composed of AlN is formed on the surface of the substrate according to the following steps. First, a catalyst is allowed to act on a first gas (step S11). As the first gas, a gas containing nitrogen, such as ammonia, can be used. As a catalyst, tungsten can be used, for example. For example, if a catalyst is allowed to act on the first gas in an environment of about 1600°C to 2200°C, the first gas is decomposed by the catalyst to generate a plurality of active species.

[0050] Next, the active species and the second gas generated in step S11 are supplied to the first layer 10 (step S12 ). As the second gas, for example, trimethylaluminum can be used.

[0051] Next, the second layer 20 is generated on the first layer 10 (step S13). The first layer 10 can be heated as needed. The temperature of the first layer 10 can be set to, for example, 420°C to 1000°C, particularly about 600°C to 700°C. The film forming time can be set to, for example, 0.5 hours to 20 hours depending on the desired thickness. For example, a ceramic structure 1 having a second layer 20 whose crystal structure is different depending on the set temperature during film formation, etc., can be obtained on the first layer 10.

[0052] [Example]

[0053] As the main phase, an AlN sintered body containing 98% by mass of AlN crystals is prepared. The AlN sintered body is processed into a first layer of 100 mm square size. It should be noted that a conductive layer containing W as a metal is arranged inside the AlN sintered body. The conductive layer is formed into a heating pattern. Then, ammonia is used as the first gas, trimethylaluminum is used as the second gas, and tungsten is used as a catalyst on the surface of one side of the first layer to form a second layer. The film forming temperature is shown in Table 1. W1 and W2 of the obtained ceramic structure are measured. W1 and W2 are shown in Table 1. In addition, as one of the comparative examples, the aforementioned AlN sintered body without a second layer is used. In the case of this sample, the half-value width of the portion corresponding to the first layer and the portion corresponding to the second layer are the same.

[0054] In addition, the cross section of the second layer of the obtained ceramic structure was used to observe the presence or absence of voids, the shape of the voids, etc. As a comparative example, a structure corresponding to the first layer and the second layer was made using a sintered body and is also recorded in Table 1. The film forming temperature and the above-mentioned measured values ​​are recorded in Table 1. It should be noted that in Table 1, blank columns are not measured or calculated.

[0055] In addition, each of the obtained samples was subjected to mirror polishing, and then a plasma etching resistance test using CF4 gas was performed to evaluate the etching rate. When the etching rate is large, the plasma etching resistance is poor.

[0056] [Table 1]

[0057]

[0058] In the case of sample No. 1, which is a comparative example in which the portion corresponding to the first layer and the second layer is made of a sintered body, the first layer is composed of approximately 100% by mass of AlN, and the content of AlN in the portion corresponding to the first layer and the second layer is 98% by mass. In addition, W1=W2, and W2>W1 cannot be satisfied. In sample No. 1, even if mirror polishing is performed, the surface roughness is greater than that of sample No. 4 as an embodiment. It is believed that this is because the crystals constituting the sintered body in sample No. 1 fall off during mirror polishing. In addition, with respect to sample No. 1, the surface roughness after the etching test is greater than that of sample No. 4 as an embodiment. In addition, with respect to sample No. 1, the change in surface roughness before and after the etching test is also greater than that of sample No. 4. It is believed that this is because the crystals present on the surface of the sintered body are degranulated during the etching test. Such degranulation may become a problem when using a ceramic structure as a component for a semiconductor manufacturing device.

[0059] In the case of samples No. 2 and 3 with a film forming temperature of 400° C. or less, the film forming speed is extremely slow and is not suitable for mass production. In addition, samples No. 2 and 3 do not satisfy 9×W1>W2. Samples No. 2 and 3 that do not satisfy 9×W1>W2 have low durability.

[0060] On the other hand, sample No. 4 as an example has excellent surface properties by mirror polishing. In addition, sample No. 4 has excellent durability in the etching test. In addition, regarding sample No. 4, it is considered that the surface roughness after etching is also very excellent, and granulation is suppressed.

[0061] In one embodiment, (1) a ceramic structure, wherein:

[0062] The ceramic structure has:

[0063] A first layer having first crystal particles; and

[0064] a second layer, which is located on the first layer and has second crystal particles,

[0065] The first crystal particles and the second crystal particles each contain one or more metal elements selected from Al, Si, Ti, Cr, Zr and Y and one or more non-metal elements selected from N, C and B.

[0066] The first crystal particles and the second crystal particles are the same compound,

[0067] When the half-value width of the peak of the Miller index of the maximum intensity of the first crystal particle in the X-ray diffraction of the first layer is set to W1, and the half-value width of the peak of the second crystal particle in the X-ray diffraction of the second layer that is the same as the Miller index is set to W2, it is 9×W1>W2>W1.

[0068] (2) In the ceramic structure of (1) above, the first crystal grains and the second crystal grains may be hexagonal crystals.

[0069] (3) In the ceramic structure of (1) or (2) above, the first crystal particles and the second crystal particles may be AlN,

[0070] The difference between W1 and W2 (W2-W1) is greater than or equal to 0.1° and less than or equal to 0.6°.

[0071] (4) In any one of the ceramic structures described in (1) to (3) above, the second layer may have a void located inside the second layer, the void being long in a thickness direction of the second layer, and both ends of the void in the thickness direction being blocked.

[0072] The void includes at least one of a first void in which one end in the thickness direction is in contact with the first layer and a second void in which the one end is separated from the first layer.

[0073] (5) In the ceramic structure of (4) above, the voids may include the first voids.

[0074] (6) In the ceramic structure of (4) or (5) above, the porosity of the second layer in a cross section parallel to the thickness direction may be 0.1 area % or more and 2 area % or less.

[0075] (7) In any one of the ceramic structures described in (4) to (6) above, the second layer may include a plurality of columnar crystals that are inclined relative to a surface of the first layer.

[0076] The gap is located between adjacent ones of the plurality of columnar crystals.

[0077] (8) In any one of the ceramic structures described in (4) to (7) above, the first layer may have irregularities on a surface facing the second layer.

[0078] One end of the gap in the thickness direction is located in the recessed portion of the first layer.

[0079] (9) In any of the ceramic structures described in (4) to (8) above, the length of the void in the direction along the surface of the first layer may be smaller at a second end farther from the first layer than at a first end in the thickness direction located on the first layer side.

[0080] (10) In any one of the ceramic structures described in (4) to (9) above, a first portion of the second layer close to the first layer may have a greater porosity than a second portion farther from the first layer than the first portion.

[0081] (11) In any one of the above-mentioned (1) to (10), the ceramic structure may include a conductive layer inside.

[0082] (12) In any one of the ceramic structures described in (1) to (11), the ceramic structure may further include a third layer located between the first layer and the second layer. The third layer contains third crystal particles of the same compound as the second layer, and when the half-value width of the peak in the X-ray diffraction of the third layer of the third crystal particles that is the same as the Miller index of the second crystal particles is set to W3, W2>W3.

[0083] Further effects and variations can be easily derived by those skilled in the art. Therefore, the broader aspects of the present disclosure are not limited to the specific detailed and representative embodiments shown and described above. Therefore, various changes can be made without departing from the spirit or scope of the general inventive concept defined by the scope of the attached claims and their equivalents.

[0084] Description of reference numerals:

[0085] 1Ceramic structure

[0086] 10First floor

[0087] 11First Crystal Particle

[0088] 20 Second Floor

[0089] 21 Second crystal particle

[0090] 21a Columnar crystal

[0091] 22 Gap

[0092] 22a First gap

[0093] 22b Second gap

[0094] 30Third floor

[0095] 31 The third crystal particle

[0096] 40 Space

[0097] 101 Surface

[0098] 101a convex part

[0099] 101b concave part

[0100] 201 First Page

[0101] 202 Second Side

[0102] 221 first end

[0103] 222 second end portion.

Claims

1. A ceramic structure, wherein: The ceramic structure has: A first layer having first crystal particles; and a second layer, which is located on the first layer and has second crystal particles, The first crystal particles and the second crystal particles each contain one or more metal elements selected from Al, Si, Ti, Cr, Zr and Y and one or more non-metal elements selected from N, C and B. The first crystal particles and the second crystal particles are the same compound, When the half-value width of the peak of the Miller index of the maximum intensity of the first crystal particle in the X-ray diffraction of the first layer is set to W1 and the half-value width of the peak same as the Miller index of the second crystal particle in the X-ray diffraction of the second layer is set to W2, 9×W1>W2>W1.

2. The ceramic structure according to claim 1, wherein: The first crystal particles and the second crystal particles are hexagonal crystals.

3. The ceramic structure according to claim 1 or 2, wherein: The first crystal particles and the second crystal particles are AlN, The difference between W1 and W2 (W2-W1) is greater than or equal to 0.1° and less than or equal to 0.6°.

4. The ceramic structure according to any one of claims 1 to 3, wherein The second layer has a gap located inside the second layer, the gap is long in the thickness direction of the second layer, and both ends of the gap in the thickness direction are blocked, The void includes at least one of a first void in which one end in the thickness direction is in contact with the first layer and a second void in which the one end is separated from the first layer.

5. The ceramic structure according to claim 4, wherein: The void has the first void.

6. The ceramic structure according to claim 4 or 5, wherein: The porosity of the second layer in a cross section parallel to the thickness direction is 0.1 area % or more and 2 area % or less.

7. The ceramic structure according to any one of claims 4 to 6, wherein the second layer has a plurality of columnar crystals inclined relative to a surface of the first layer, The gap is located between adjacent ones of the plurality of columnar crystals.

8. The ceramic structure according to any one of claims 4 to 7, wherein The first layer has projections and depressions on a surface opposite to the second layer, One end of the gap in the thickness direction is located in the recessed portion of the first layer.

9. The ceramic structure according to any one of claims 4 to 8, wherein The length of the gap in the direction along the surface of the first layer is smaller at a second end farther from the first layer than at a first end in the thickness direction located on the first layer side.

10. The ceramic structure according to any one of claims 4 to 9, wherein A first portion of the second layer close to the first layer has a void ratio greater than a second portion of the second layer farther from the first layer than the first portion.

11. The ceramic structure according to any one of claims 1 to 10, wherein The ceramic structure has a conductive layer inside.

12. The ceramic structure according to any one of claims 1 to 11, wherein The ceramic structure further comprises a third layer located between the first layer and the second layer, The third layer contains third crystal particles of the same compound as the second layer, When the half-value width of the peak identical to the Miller index of the second crystal grain in the X-ray diffraction of the third layer of the third crystal grain is defined as W3, W2>W3.

Citation Information

Patent Citations

  • Manufacture of thin film by catalytic CVD method and device therefor

    JP1988040314A

  • Coated member

    JP1995180057A

  • Electrostatic chuck

    JP2020053579A